PEMBERDAYAAN MASYARAKAT MELALUI BUDIDAYA MADU GALO GALO (TRIGONA SP) DAN PENDIRIAN TAMAN TANAMAN OBAT KELUARGA DI NAGARI TIUMANG KABUPATEN DHARMASRAYA - Ediset, Ediset; Rusdimansyah, Rusdimansyah; Ismet, Ismet; Saputra, Dendi Adi; Anas, Amrizal (LPPM (Lembaga Penelitian dan Pengabdian kepada Masyarakat) Universitas Andalas, 2024)
The purpose of the activity is to educate the Women Farmers Group to have the knowledge and skills about galo galo honey cultivation (Trigona sp) and the establishment of a Family Medicinal Plant Garden in Nagari Tiumang, Tiumang District, Dharmasraya Regency. The implementation method for each activity is carried out in several systematic stages, namely the socialization stage, the demonstration plot stage and the mentoring stage. The results of Galo galo (Trigona sp) cultivation education activities are Women Farmers Group already has knowledge and skills on Galo galo cultivation, already has 4 Galo galo honey colonies, 2 colonies for the Trigona Itema type and 2 colonies for the Trigona Minangkabau type, where 2 colonies of the Trigona Itema type have been harvested and produce honey production as much as 250-300 grams / colony. In addition, Women Farmers Group and the community also have a 15 m x 25 m Family Medicinal Plants garden which contains 5 types of medicinal plants, such as Ginger (Zingiber officinale), Turmeric (Curcuma longa), Curcumalonga (Curcuma xanthorrhiza), Aloe vera (Aloe vera) and Betel Leaf (Piper betle). Conclusion is this service activity has gone well where the target already has a Galo galo honey (Trigona sp) business and a Toga garden, so that it will be able to realize the occurrence of independence and empowerment in the community, especially for members of Women Farmers Group orchids and the community in Nagari Tiumang, Dharmasraya Regency.